Exploring Ethnomedicine Plants Used By The Indigenous Communities In Terengganu, Malaysia: Human Health And The Environment - Muhammad Fuad Abdullah; Elizabeth Pesiu; Mohd Iqbal Mohd Noor; Azniza Ahmad Zaini; Amirah Azzeri; Mohd Tajuddin Abdullah (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus/MyCite